2020
DOI: 10.1186/s12985-020-01331-z
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of multiple reassortant H6 subtype avian influenza viruses in wild birds in eastern China, 2016–2017

Abstract: Background H6 subtype influenza viruses were prevalent in domestic poultry and wild birds, which also could pose potential threat to humans. However, little is known about the prevalence of H6 subtype viruses in wild birds in eastern China, a crucial stopover or wintering site for migratory wild birds along the East Asian-Australasian Flyway. Methods During the routine surveillance in 2016–2017, H6 subtype AIVs positive samples were identified, and the representative strains were selected for further sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In our study, K6 showed the highest viral titer of 10 6.37 log 10 TCID 50 at 36-48 hpi, which corresponded with the previous results that had shown H6 viruses to grow efficiently and reach a peak of 10 5 log 10 TCID 50 at 36 hpi in MDCK cells [9]. Moreover, the K6 virus was found to replicate efficiently in lungs without prior adaptation; however, it was not lethal in mice, which is consistent with other publications that examined the toxicity in mice, induced by H6-AIV [71]. The mice challenged intranasally with 10 6 EID 50 exhibited slight loss in body weight, and viral load in the lung was found to be 4.82 log 10 TCID 50 /100 mg. Alternatively, the A/aquatic bird/Korea/CN5/2009 (H6N5) strain causes illness and lethality in mice, with severe clinical signs, including significant weight loss, ruffled fur, lethargy, and ataxia, with 100% mortality noted within 7 days [12].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, K6 showed the highest viral titer of 10 6.37 log 10 TCID 50 at 36-48 hpi, which corresponded with the previous results that had shown H6 viruses to grow efficiently and reach a peak of 10 5 log 10 TCID 50 at 36 hpi in MDCK cells [9]. Moreover, the K6 virus was found to replicate efficiently in lungs without prior adaptation; however, it was not lethal in mice, which is consistent with other publications that examined the toxicity in mice, induced by H6-AIV [71]. The mice challenged intranasally with 10 6 EID 50 exhibited slight loss in body weight, and viral load in the lung was found to be 4.82 log 10 TCID 50 /100 mg. Alternatively, the A/aquatic bird/Korea/CN5/2009 (H6N5) strain causes illness and lethality in mice, with severe clinical signs, including significant weight loss, ruffled fur, lethargy, and ataxia, with 100% mortality noted within 7 days [12].…”
Section: Discussionsupporting
confidence: 91%
“…Wild bird migration and live poultry trade play important roles for virus transmission. Frequent gene reassortments were observed between viruses from poultry and wild birds ( 52 , 55 - 66 ), which increased the genetic diversity of H3 AIVs and contributed genes to other subtype AIVs such as HPAIV H5 ( 67 - 68 ). Despite the relatively improved surveillance studies having been performed in recent years in China, our understanding of the H3 AIVs transmission and evolution is still limited, especially in intercontinental migratory birds.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by studies that suggest that H6-subtype IAVs are the most frequently isolated subtypes from wild waterfowl especially in Asia 20 . A study from China reported that 11.07% of the isolates from wild birds in 2016–2017 were of the H6 subtype, making H6 the most predominant subtype in that study 21 . In our study, IAVs of the H6 subtype were likewise the most prevalent over the winter of 2016–2017, which may indicate similar distributions of IAV subtypes along the EAAF that year.…”
Section: Discussionmentioning
confidence: 88%